Diseño de un plan de auditoría para Sistemas de Gestión de Seguridad y Salud en el Trabajo en los procesos misionales de una empresa de fundición de metales (2015)
This degree project presents the design of an audit plan for the operation of a metal smelting company based on Occupational Health and Safety Management Systems based on Decree 1443 of 2014 and the NTC OHSAS 18001: 2007 focused on companies in the metalworking sector, in order to establish the common requirements to these standards and from there, obtain guidelines to demonstrate that the requirements that apply to the operation are related to the technical aspects of hazard identification, assessment of risks, determination of controls and compliance with the technical and legal aspects associated with the process. This is how, as in the first chapters, reference is made to the economic activity to which the metal smelting process belongs, its growth in the National industry and the statistics of accidents and occupational diseases that it presents. Likewise, it continues with the identification of the risk factors associated with the operation and the legal aspects applicable to it. At the end of the work, the audit plan, the checklist and the checklist are presented, the methodology and the proposed criteria are established to verify the level of compliance with the requirements of the two management models studied, as well as the legal and technical compliance applicable.